2013
DOI: 10.1038/msb.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Timescales and bottlenecks in miRNA‐dependent gene regulation

Abstract: Application of a kinetic model of miRNA-mediated gene regulation to experimental data sets shows that the timescale of regulation is slower than previously assumed, due to bottlenecks imposed by miRNA turnover in the RNA-induced silencing complex and by slow protein decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 56 publications
1
62
0
Order By: Relevance
“…miRNA binding to the CDS mainly leads to translation inhibition Ribosome protected fragment (RPF) sequencing experiments can be used to quantify and compare translation efficiency genome-wide across experimental conditions [37]. Compared to joint mRNA profiling and quantitative proteomics experiments [18,32], RPF sequencing provides a broader coverage of the genome and directly measures the regulatory impact of miRNAs on translation, thereby circumventing the issue of protein stability which delays the regulatory impact of miRNAs [16,18,38]. Guo et al [16] performed RPF sequencing following miRNA transfection in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA binding to the CDS mainly leads to translation inhibition Ribosome protected fragment (RPF) sequencing experiments can be used to quantify and compare translation efficiency genome-wide across experimental conditions [37]. Compared to joint mRNA profiling and quantitative proteomics experiments [18,32], RPF sequencing provides a broader coverage of the genome and directly measures the regulatory impact of miRNAs on translation, thereby circumventing the issue of protein stability which delays the regulatory impact of miRNAs [16,18,38]. Guo et al [16] performed RPF sequencing following miRNA transfection in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some minimal models, for instance, a model for miRNA action in competing endogenous RNA (ceRNA) networks (Gérard and Novák 2013), only include reversible binding of miRNA and mRNA and degradation of the complex. Others include details of miRNA biogenesis, formation of RISC (Hausser et al 2013), stoichiometric degradation of complex, selective degradation resulting in "catalytic," or nonstoichiometric return of miRNA from the complex (Gokhale and Gadgil 2012;Klironomos and Berg 2013), and details of translation by the bound mRNA (Zinovyev et al 2013). An excellent review paper by Zhdanov discusses almost all the kinetic models until 2011 (Zhdanov 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Noncanonical targets have also been reported, although in much smaller numbers (Lal et al 2009;Shin et al 2010;Chi et al 2012;Loeb et al 2012;Helwak et al 2013;Grosswendt et al 2014). Different studies have reported various degrees of miRNA-induced mRNA destabilization and translational inhibition (Baek et al 2008;Selbach et al 2008;Hendrickson et al 2009;Guo et al 2010;Huntzinger and Izaurralde 2011;Jovanovic et al 2012;Stadler et al 2012;Hausser et al 2013). A few recent studies have shown that translational inhibition precedes mRNA destabilization (Bazzini et al 2012;Djuranovic et al 2012), although a report argued that miRNA-induced poly(A)-tail shortening can affect translational repression and mRNA destabilization differently in different developmental stages (Subtelny et al 2014).…”
mentioning
confidence: 99%